PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBANTUAN CURIPOD PADA MATERI TEKS BIOGRAFI KELAS XI SMK MADANI MARINDAL I - Siti Hajrah; Ali Ali; Rita Rita (BEST Journal (Biology Education, Sains and Technology), 2025)
This study aimed to investigate the development and feasibility and effectiveness of procedure worksheet assisted by curipod on biographical text material of class X at SMK Madani Marindal 1. It used a Research and Development (RD) method using the Reasearch and Development  model, that consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The population and sample of this study include 65 students from three different classes: Computer and Network Engineering (TKJ) and Automotive Engineering (TBSM).The results indicated the developed teaching material is deemed feasible. The first content expert rated as “Highly Feasible” or 90 %, while the second content expert obtained “Feasible” or 82%. The first design expert rated as “Highly Feasible” or 80%, and the second design expert rated as “Feasible” or 80%. The teacher’s assessment obtained “Highly Feasible” or 91%. The field implementation test involving 44 students across the three classes (35 TKJ), of class X at SMK Madani Marindal 1,obtained “Highly Feasible” or 85,82%. and the results of the trial of the student worksheets were categorized as "Effective" with a percentage before using the student worksheets of 64% and after using the student worksheets, the students got and the results of the trial of the student worksheets were categorized as "Effective" with a percentage before using the student worksheets of 64% and after using the worksheet, students got a score of 83.7% with an increase of 20%